Maankäyttölajien luokittelujen ja määritelmien yhtenäistämisestä - Pihkala, K. U. (Agricultural and Food Science, 1946)
The instructions of the Finnish agricultural statistics, Board of Survey and communal taxation measurements for classification of land utilization types differ from each another, thus making it difficult to compare and to control the preliminary data of statistics. Definitions of land utilization classes have been inadequate causing uncertainty in information about area. In the present investigation a proposal has been made for a new classification which would be better comparable than the former one with the classification of the Board of Survey as well as for a more detailed definition of land utilization types. The aim of the definitions has been to attain such characteristic features which enable drawing of a definite line between different land utilization types even when persons with little training are employed as collectors of the required information. Besides, the principle adhered to, when determining the class of land utilization, has been not to take into account the temporary use of land outside its regular use. The land area belonging to one agricultural enterprise (excluding waters) is divided according to the new proposal to the following main groups: I. Agricultural land 11. Cultivable land 111. Actual forest land IV. Waste land. The agricultural land is divided into the following groups according to its use 1. Garden (orchard and vegetable garden) 2. Field. 3. Permanent pasture on fields 4. Meadow (natural meadow). 5. Cleared pasture. 6. Building site, roads, etc. The cleared pastures include enclosed treeless and stumpy pasture lands and in addition to these natural meadows similarly enclosed and permanently used as pasture. The cultivable land is divided into cultivable open peat moss and cultivable forest land. The latter together with the actual forest land forms the group which corresponds to the earlier forest land group. Proposed practice makes comparison with surveying areas easier.